2017
DOI: 10.1038/s41598-017-02950-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between diffusion tensor imaging and levels of consciousness in patients with traumatic brain injury: a systematic review and meta-analysis

Abstract: Traumatic brain injury (TBI) often leads to impaired consciousness. Recent diffusion tensor imaging studies associated consciousness with imaging metrics including fractional anisotropy (FA) and apparent diffusion coefficient (ADC). We evaluated their correlations and determined the best index in candidate regions. Six databases were searched, including PubMed and Embase, and 16 studies with 701 participants were included. Data from region-of-interest and whole-brain analysis methods were meta-analysed separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 52 publications
4
22
0
Order By: Relevance
“…A meta-analysis recently demonstrated that FA correlates better with consciousness levels compared with other MRI tools like apparent diffusion coefficient (ADC) in patients with traumatic brain injury (TBI). [20] However, it also showed that the degree of correlation varies among brain regions. Multiple manual and automatic protocols have been reported for the reconstruction of the ARAS with DTT aiming to correlate radiological findings with the level of consciousness after a TBI or stroke.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis recently demonstrated that FA correlates better with consciousness levels compared with other MRI tools like apparent diffusion coefficient (ADC) in patients with traumatic brain injury (TBI). [20] However, it also showed that the degree of correlation varies among brain regions. Multiple manual and automatic protocols have been reported for the reconstruction of the ARAS with DTT aiming to correlate radiological findings with the level of consciousness after a TBI or stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Damage to the hippocampal commissure, combined with the loss of visuospatial and auditory information transfer in splenial pathology and further disintegration of the cerebral network, may lead to changes in consciousness. Using DTI, Zhang et al determined that consciousness levels correlated strongly with a reduction of fractional anisotropy value in the corpus of the CC and moderately in the splenium, corresponding with increased demyelination [28]. Acute severing of the crossing fibers following head trauma has been shown to lead to altered mental status and even coma [29].…”
Section: Consciousnessmentioning
confidence: 99%
“…Over the last 20 years many studies have investigated the ability of clinical signs and technologically based physiological tests to detect and measure awareness. There have been at least five relevant systematic reviews [17][18][19][20][21], shown in Table 2.…”
Section: The Evidence: Signs and Testsmentioning
confidence: 99%